Relevant Genes Linked to Virulence Are Required for Salmonella Typhimurium to Survive Intracellularly in the Social Amoeba Dictyostelium discoideum - Riquelme, Sebastián; Varas, Macarena; Valenzuela, Camila; Velozo, Paula; Chahin, Nicolás; Aguilera, Paulina; Sabag, Andrea; Labra, Bayron; Álvarez, Sergio A.; Chávez, Francisco P.; Santiviago, Carlos A. (Frontiers in Microbiology, 2016)
The social amoeba Dictyostelium discoideum has proven to be a useful model for studying relevant aspects of the host-pathogen interaction. In this work, D. discoideum was used as a model to study the ability of S. Typhimurium to survive in amoebae and to evaluate the contribution of selected genes in this process. To do this, we performed infection assays using axenic cultures of D. discoideum co-cultured with wild-type S. Typhimurium and/or defined mutant strains. Our results confirmed that wild-type S. Typhimurium is able to survive intracellularly in D. discoideum. In contrast, mutants ΔaroA and ΔwaaL are defective in intracellular survival in this amoeba. Next, we included in our study a group of mutants in genes directly linked to Salmonella virulence. Of note, mutants ΔinvA, ΔssaD, ΔclpV and ΔphoPQ also showed an impaired ability to survive intracellularly in D. discoideum. This indicates that S. Typhimurium requires a functional biosynthetic pathway of aromatic compounds, a lipopolysaccharide containing a complete O-antigen, the type III secretion systems (T3SS) encoded in SPI-1 and SPI-2, the type VI secretion system (T6SS) encoded in SPI-6 and PhoP/PhoQ two-component system to survive in D. discoideum. To our knowledge, this is the first report on the requirement of O-antigen and T6SS in the survival of Salmonella within amoebae. In addition, mutants ΔinvA and ΔssaD were internalized in higher numbers than the wild-type strain during competitive infections, suggesting that S. Typhimurium requires the T3SS encoded in SPI-1 and SPI-2 to evade phagocytosis by D. discoideum. Altogether, these results indicate that S. Typhimurium exploits a common set of genes and molecular mechanisms to survive within amoeba and animal host cells. The use of D. discoideum as a model for host-pathogen interactions will allow us to discover the gene repertoire used by Salmonella to survive inside the amoeba and to study the cellular processes that are affected during infection.